A novel alternative energy trading mechanism for different users considering value-added service and price competition. (October 2022) - Dai, Yeming; Yang, Yuqing; Leng, Mingming
Highlights: The unified mode of purchase and sale of integrated power retailer is studied. The integrated power retailers obtain traditional electricity in bidding form. The integrated power retailers can buy natural gas energy when the bids fail. A leader–follower game is developed between power retailers and classified users. The price competition and added-value service are considered at the same time. Abstract: In the context of integrated energy substitution and retail side liberalization, we develop a novel alternative energy trading mechanism in the presence of price competition and value-added service to study the purchase and sale strategies for integrated energy retailers. Under the mechanism, the retailer first joins a second-price sealed auction to make an optimal electricity purchase. If the retailer's purchase bid fails, the retailer procures natural gas from a natural gas company to generate electricity. The retailer then sells the electricity to different users who buy according to their own types, which is modeled a leader–follower game for multiple retailers and classified users. Using a computational data, we design a distributed algorithm to solve the leader–follower game. The simulation results verify the convergence of proposed algorithm. Moreover, our sensitivity analysis indicates that the natural gas distribution rate and its conversion rate with respect to electricity are important to the power retailer's profit in terms of energy loss rate and capacity rate. Compared with the non-demand response model, the novel alternative energy trading mechanism can help the power retailer reduce peaks and fill valleys to a certain extent, achieving an effective system balance of energy distribution and maximizing the power retailer's profit and users' utilities.